Pelatihan Kemampuan Komunikasi Bahasa Inggris Sebagai Kesiapan Ekonomi Bagi Siswa PIK R Di SMP Muhammadiyah I Rawabening - Zulaikah Zulaikah; Hatuti Retno K.; Mursilah Mursilah (IAI Darussalam, 2021)
This activities starts from the PIK R group which did not create activities mainly related to life skills for economic preparation for adolescents in planning a happy and prosperous family life. Lack of knowledge, attitudes, behavior of adolescents about life skills (English language ability) to be practiced so that growth and development to the fullest in order to realize the generation of planning. the low knowledge of family life readiness especially economic readiness, the low Life Skill especially English language skills is an important issue being faced. The solution offered from these problems is continuous training on Life Skills and English communication skills for PIK R students. The method used is the silent way, with consonant vocal recitation correctly. The results of this devotion were very high enthusiasm from the participants with their enthusiasm for learning, designing creativity and becoming a problem solver for their educational problems. Characterized by the increased ability of English communication, especially in terms of vocabularies about economic learning.